Anti-wetting ability of the hydrophobic surface decorated by submillimeter grooves. (October 2020) - Yuan, Zhicheng; Wen, Jian; Matsumoto, Mitsuhiro; Kurose, Ryoichi
Highlights: Surface hydrophobicity is improved by decorating submillimeter grooves. Asymmetric spreading and "jump-stick" are observed on textured surfaces. Two bubble entrapment mechanisms are investigated. A mathematical model is formulated to predict the maximum spreading diameter. Abstract: In the study, the effect of submillimeter groove width and impact velocity on the hydrophobicity of a textured substrate is investigated via three-dimensional direct numerical simulations. To study the droplet dynamics, the coupled level set and volume of the fluid method (CLSVOF) incorporated with the dynamic contact angle (DCA) model and contact angle implementation technology are employed. Results indicate that the increasing groove width from 0.0 to 0.4 mm yields decreasing droplet spreading diameter, thereby reducing the contact time between liquid and solid. Although the contact time decreases rapidly with the increase of initial impact velocity from 0.0 to 0.4 m/s, the continually increasing velocity does not exhibit a further effect. In particular, "jump stick" behavior is observed in the groove vertical direction when the liquid migrates from the contacting ridge to the next one, thereby causing asymmetric spreading as a result of the free movement in the groove parallel direction. Furthermore, a donut-like shape is demonstrated at the maximum spreading state, while at the bouncing stage, surrounding liquid retracts to the impact center and a small air bubble is trapped during the convergence. Additionally, the mathematical model, considering the impregnating liquid in grooves, is formulated to predict the droplet maximum spreading diameter in the groove vertical direction. Graphical abstract: The donut-like shapes are observed on both the flat and the patterned surface. A perfect circle can be seen on the flat, whereas an elliptical shape on the decorated substrate is illustrated owing to the asymmetric spreading. It occurs because liquid spreads freely in the groove parallel direction, but migration is suppressed in the vertical direction and thus the surface anti-wetting ability is improved. Image, graphical abstract